2017
DOI: 10.21037/atm.2017.04.33
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ABO blood group on sports performance

Abstract: Background: Despite being a recessive trait, the O blood group is the most frequent worldwide among the ABO blood types. Since running performance has been recognized as a major driver of evolutionary advantage in humans, we planned a study to investigate whether the ABO blood group may have an influence on endurance running performance in middle-aged recreational athletes. Results: In univariate analysis, running performance was significantly associated with age and weekly training, but not with body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Concerning infectious diseases, the O group could have special protection derived from anti-A/anti-B actions of humoral innate immunity [ 57 , 58 ]. In addition, the O group had some physiological advantages such as endurance running, compared with non-O-groups [ 59 ]. ABO differences in respect to health and disease are not entirely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning infectious diseases, the O group could have special protection derived from anti-A/anti-B actions of humoral innate immunity [ 57 , 58 ]. In addition, the O group had some physiological advantages such as endurance running, compared with non-O-groups [ 59 ]. ABO differences in respect to health and disease are not entirely understood.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of distribution of the ABO and Rh blood groups varies between races. O blood group is more common around the world 6 , although studies have reported higher frequency rates of the A and Rh (+) blood groups in Turkey. 7,8 ABO antigens are complex carbohydrate molecules that are expressed on the surfaces of red blood cells, but also on the epithelium, neurons, platelets, and vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 98%
“…The TCI, a top-down personality model, is often used to examine genetic dispositions [35][36]. This personality test built a model for temperament with a physiological basis in the background.…”
Section: Results Of the Non-big Five Personality Testmentioning
confidence: 99%